Reflexiones en torno a la reputación y su protección jurídica - Angulo Arana, Pedro Miguel (2023)
In ancient Rome, to protect the State and prevent some people from accessing important positions, institutions such as infamy and ignominy were developed. In the Middle Ages, the concept of honor will arise to generate developed. In the Middle Ages, the concept of honor will arise to generate power and protect it through alliances.In this way, in light of the historical power evolution of concepts such as reputation and honor and their jurisprudential evolution treatment, it is concluded that it is pertinent to differentiate the defense of honor and the defense of good reputation between the figure of injury and the figure of defamation.